1989
DOI: 10.1038/342299a0
|View full text |Cite
|
Sign up to set email alerts
|

X-ray analysis of HIV-1 proteinase at 2.7 Å resolution confirms structural homology among retroviral enzymes

Abstract: Knowledge of the tertiary structure of the proteinase from human immunodeficiency virus HIV-1 is important to the design of inhibitors that might possess antiviral activity and thus be useful in the treatment of AIDS. The conserved Asp-Thr/Ser-Gly sequence in retroviral proteinases suggests that they exist as dimers similar to the ancestor proposed for the pepsins. Although this has been confirmed by X-ray analyses of Rous sarcoma virus and HIV-1 proteinases, these structures have overall folds that are simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
253
0
3

Year Published

1992
1992
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 451 publications
(261 citation statements)
references
References 20 publications
5
253
0
3
Order By: Relevance
“…Figure 4 shows details of the interface region, from which it is clear that Leu-6 enables the two potentially separate cores to merge. Although the detection of a single hydrophobic core leads to this domain assignment, a single core passing through the interface is in line with earlier analyses of the HIV proteinase, which also noted this characteristic (Lapatto et al, 1989).…”
Section: Assignment Difficulties With Pepsin and Lactate Dehydrogenasesupporting
confidence: 87%
See 1 more Smart Citation
“…Figure 4 shows details of the interface region, from which it is clear that Leu-6 enables the two potentially separate cores to merge. Although the detection of a single hydrophobic core leads to this domain assignment, a single core passing through the interface is in line with earlier analyses of the HIV proteinase, which also noted this characteristic (Lapatto et al, 1989).…”
Section: Assignment Difficulties With Pepsin and Lactate Dehydrogenasesupporting
confidence: 87%
“…Figure 4 shows details of the interface region, from which it is clear that Leu-6 enables the two potentially separate cores to merge. Although the detection of a single hydrophobic core leads to this domain assignment, a single core passing through the interface is in line with earlier analyses of the HIV proteinase, which also noted this characteristic (Lapatto et al, 1989).A second case where automated assignments yield unanticipated results is in lactate dehydrogenase, where core residues also span the domain interface. As a result, the Rossmann fold domain is merged with the second domain (see Appendix 1).…”
supporting
confidence: 81%
“…5A; Kinemage 2). Although the apoenzyme of HIV-1 PR is strictly symmetric under conditions of the investigation of its crystals reported previously (Lapatto et al, 1989;Navia et al, 1989;Wlodawer et al, 1989), most of the inhibitors studied so far are asymmetric, and thus the two molecules in the protein dimer of the resulting complex are nonequivalent. It was reported that this asymmetry is present even in the complexes of protease with quasisymmetric inhibitors Bone et al, 1991).…”
Section: I F O Imentioning
confidence: 95%
“…The substrate binding cleft and the catalytic aspartic residues are located between these lobes (for review, see Davies [1990]). On the other hand, the retroviral aspartic proteases, including the HIV protease, are homodimers with the substrate binding cleft and the active-site aspartic residues equally contributed by the two monomers (Foundling et al, 1989;Lapatto et al, 1989;Miller et al, 1989;Wlodawer et al, 1383Fitzgerald et al, 1990). It has been proposed that the internally homologous lobes of pepsin and other eukaryotic aspartic proteases are evolutionarily derived by gene duplication and fusion, and that a primordial aspartic protease would have a homodimeric structure (Tang et al, 1978).…”
Section: ~ ~~~~mentioning
confidence: 99%